Case Report: Effective use of eculizumab in treating recurrent atypical HUS following renal transplantation triggered by SARS-CoV-2 infection - Yang, Zhe; Chen, Dongdong; Xu, Xiaoyu; Yang, Xiaoqing; Du, Wenzhi; Zhang, Minrui; Li, Xianduo; Wang, Jianning (Frontiers in Medicine, 2025)
Atypical hemolytic uremic syndrome (aHUS) is a severe post-transplant complication associated with a high risk of graft loss and mortality. Based on its pathophysiological mechanism, aHUS can be classified into recurrent aHUS (reactivation post-transplantation) and de novo aHUS (new-onset disease after transplantation). This study reports a case of a 52-year-old kidney transplant recipient who developed recurrent aHUS 10 months post-transplantation, triggered by SARS-CoV-2 infection. Genetic analysis revealed mutations in complement-related genes CFHR and C3. Following the diagnosis, the patient received a course of eculizumab induction therapy (900 mg/week for the first 4 weeks), followed by long-term maintenance therapy (900 mg every 2 weeks). Significant clinical improvement was observed, including stabilization of blood pressure, normalization of hemoglobin and lactate dehydrogenase (LDH) levels, an increase in platelet count, and a urine output exceeding 2,000 mL per day. The patient continued regular follow-up after discharge, with stable graft function. This case highlights the potential role of SARS-CoV-2 and other infections as triggers for aHUS recurrence in kidney transplant recipients and further supports the efficacy of eculizumab in treating recurrent aHUS. Furthermore, this study underscores the importance of precise immune risk stratification and early intervention in the effective management of aHUS recurrence.